Evaluation of Opinion about the Clinical Refresher Courses Conducted for the Teachers of Undergraduate Medical Institutes in Bangladesh - Talukder, MHK; Chowdhury, Fatema P; Shuvra, MR (TAJ: Journal of Teachers Association, 2009)
This descriptive type of cross-sectional study was carried out among the faculty members of different government and non government medical colleges selected by simple random sampling from October 2003 to March 2004 using self-administered structured questionnaires - one for the participants and another for their Heads of the departments to evaluate the opinion about the clinical refresher course conducted for them which was organized by WHO & DGHS at the conference room of DGHS. Sample size was 237.From the participants perspectives study revealed that the contents of the refresher clinical course were adequate, 71 (38.6%) respondents strongly agreed that speakers of the workshop were competent, 11 (6.0%) respondents strongly agreed that supplied handouts were adequate but 52 (28.3%) strongly disagreed about it. 45 (24.5%) respondents strongly agreed that audio-visual aids were used adequately, 21(11.4%) disagreed and 4(2.2%) strongly disagreed about it. 47(25.5%) respondents strongly agreed that the duration of the workshop was adequate, 92(50.0%) also agreed but 29(15.8%) respondents disagreed with it. 84(45.7%) respondents strongly agreed that the environment of the workshop was good and 91 (49.5%) also agreed with it. 177 (96.2%) respondents asserted ‘yes'- that attending these workshops benefited them, 178 (96.7%) respondents asserted ‘yes - that such workshop is essential for them every year. Perspectives of departmental Heads study also revealed that out of 53 respondents 49(92.5%) agreed that the clinical refresher course conducted for the teachers of their departments has enriched their knowledge about the subject concerned but 4(7.5%) responded negatively. 35 (66.0%) respondents agreed that the conducted clinical refresher course for the teachers of their departments helped to develop their skill and 18(34.0%) respondents told that it did not help to develop skills of the teachers of their departments. Out of 53 respondents 49 (92.5%) mentioned that the clinical refresher course conducted for the teachers of their departments could make an attitudinal change among the teachers in their teaching for using updated knowledge and skill of the subject. 46(86.8%) respondents agreed that the clinical refresher course conducted for their teachers has helped to think about their continuing professional development (CPD) through continuing medical education (CME) but 7(13.2%) respondents replied negatively. It can be concluded that the evaluation of opinion about clinical refresher course conducted for the teachers of different medical institutes in Bangladesh was positive and inspiring. doi: 10.3329/taj.v17i1.3487 TAJ 2004; 17(1) : 31-37